The Application of the Marind Tribe's Life Principle of Compassion With the PBL Model to Foster Student Character Elementary School In Merauke - Ermelinda Agnes Gunu Pure; Wahira Wahira; Kartini Marzuki (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyse the effect of applying the Problem-Based Learning (PBL) model based on the Marind Tribe's life principles on the development of students' compassion. The approach used was quantitative with a quasi-experiment design using Nonequivalent (Pretest and Posttest) Control Group Design. The research subjects consisted of 120 students at SD YPPK St Tarsisius Biankuk, SD YPPK St Fransiskus Xaverius I, and SD YPPK Sta. Theresia Buti Merauke, which were divided into experimental and control classes. Data analysis was conducted using the Independent Sample t-test with the help of SPSS IBM 23. The results showed that the application of the PBL model significantly improved students' compassion attitudes, with a calculated t value (50.842) > t table (1.981) and p-value (0.000) < 0.05, indicating a significant difference between the experimental and control classes.